Evaluasi Kinerja Perbankan Dalam Menerapkan Prinsip-Prinsip Good Corporate Governance - Sari, Hanifa Aulia; Alfitra, Dimas; Harisma, Fadilla; Yanto, Heri; C, Cisia; Yani, Fitri (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In this journal, evaluation of banking performance in implementing the principles of Good Corporate Governance (GCG) is discussed. GCG has become a very significant aspect in the banking sector, especially after the global financial crisis in 2008. This research aims to evaluate the extent to which banks have succeeded in implementing GCG principles and the impact on their performance. The research methods used include literature studies and analysis of historical data on banking performance. The research results show that banks that implement GCG principles well tend to have more positive performance in the long term. They have lower levels of risk, greater trust from customers, and better relationships with shareholders and regulators. This research provides valuable insight into the significance of GCG in the banking industry and its positive impact on banking performance. By implementing good GCG, banks can achieve long-term sustainability and reduce the risks associated with their operations.